Hyperthermia adds to trabectedin effectiveness and thermal enhancement is associated with BRCA2 degradation and impairment of DNA homologous recombination repair. Issue 2 (25th March 2016) - Harnicek, Dominique; Kampmann, Eric; Lauber, Kirsten; Hennel, Roman; Cardoso Martins, Ana Sofia; Guo, Yang; Belka, Claus; Mörtl, Simone; Gallmeier, Eike; Kanaar, Roland; Mansmann, Ulrich; Hucl, Tomas; et al.
Abstract : The tetrahydroisoquinoline trabectedin is a marine compound with approved activity against human soft‐tissue sarcoma. It exerts antiproliferative activity mainly by specific binding to the DNA and inducing DNA double‐strand breaks (DSB). As homologous recombination repair (HRR)‐deficient tumors are more susceptible to trabectedin, hyperthermia‐mediated on‐demand induction of HRR deficiency represents a novel and promising strategy to boost trabectedin treatment. For the first time, we demonstrate enhancement of trabectedin effectiveness in human sarcoma cell lines by heat and characterize cellular events and molecular mechanisms related to heat‐induced effects. Hyperthermic temperatures (41.8 or 43°C) enhanced significantly trabectedin‐related clonogenic cell death and G2/M cell cycle arrest followed by cell type‐dependent induction of apoptosis or senescence. Heat combination increased accumulation of γH2AX foci as key marker of DSBs. Expression of BRCA2 protein, an integral protein of the HRR machinery, was significantly decreased by heat. Consequently, recruitment of downstream RAD51 to γH2AX‐positive repair foci was almost abolished indicating relevant impairment of HRR by heat. Accordingly, enhancement of trabectedin effectiveness was significantly augmented in BRCA2‐proficient cells by hyperthermia and alleviated in BRCA2 knockout or siRNA‐transfected BRCA2 knockdown cells. In peripheral blood mononuclear cells isolated from sarcoma patients, increased numbers of nuclear γH2AX foci were detected after systemic treatment with trabectedin and hyperthermia of the tumor region. The findings establish BRCA2 degradation by heat as a key factor for a novel treatment strategy that allows targeted chemosensitization to trabectedin and other DNA damaging antitumor drugs by on‐demand induction of HRR deficiency. Abstract : What's new? Trabectedin kills tumor cells by binding to DNA and inducing double‐strand breaks. An impaired DNA repair mechanism makes a tumor more susceptible to trabectedin treatment, and heat inactivates certain proteins involved in DNA double‐strand break repair. The authors found that heat improves trabectedin‐induced cell death in sarcoma cell lines. This enhancement results from the degradation of BRCA2, they conclude: on‐demand inhibition of DNA repair by heat is a promising strategy to improve effectiveness of trabectedin.